FROM CLICKS TO EXCLUSIVITY: SOCIAL MEDIA ALGORITHMS AND RELIGIOUS POLARIZATION AMONG MADRASAH YOUTH IN JAKARTA - Ade Fitriyanti; Abdul Hamid Busthami Nur (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2026)
The growth of algorithm-driven social media has reshaped how Muslim youth in Indonesia access religious knowledge and form religious attitudes, raising concerns for religious moderation and social harmony in a plural society. This study examines the influence of social media algorithmic exposure on religious polarization among madrasah students and explores how this dynamic relates to authority, openness, and interfaith implications. Employing a mixed-methods sequential explanatory design, the quantitative phase surveyed 300 students from eight madrasahs (Madrasah Aliyah and Tsanawiyah) in East and North Jakarta selected through proportionate stratified random sampling, using a validated five-point Likert questionnaire (Cronbach's alpha = 0.86). The qualitative phase comprised in-depth interviews with twelve students and three Islamic Education teachers, which were analysed thematically and integrated with the survey results through a joint display. Simple linear regression showed a significant positive effect of algorithmic exposure on religious polarization (β = 0.559; R² = 0.312; p < 0.001). Students with higher exposure exhibited more exclusive attitudes and lower openness to differing views, while recommendation systems on YouTube and TikTok reinforced echo chambers and shifted religious authority from teachers toward digital figures. The study proposes the concept of “algorithmic religiosity” to describe a religious orientation shaped by the selection and amplification logic of platforms. Because the design is correlational and exposure was self-reported, the findings imply, rather than directly demonstrate, risks to interfaith openness; a concrete implication is embedding algorithmic literacy and religious moderation content within madrasah curricula, delivered in formats able to compete with the engagement logic of social media platforms. Abstrak Perkembangan media sosial berbasis algoritma telah mengubah cara remaja Muslim Indonesia mengakses pengetahuan agama dan membentuk sikap keberagamaan, sehingga menimbulkan tantangan bagi moderasi beragama dan keharmonisan sosial dalam masyarakat yang plural. Penelitian ini menganalisis pengaruh paparan algoritma media sosial terhadap polarisasi keagamaan di kalangan siswa madrasah serta mengkaji keterkaitannya dengan otoritas, keterbukaan, dan implikasi antaragama. Dengan desain mixed-methods sequential explanatory, tahap kuantitatif mensurvei 300 siswa dari delapan madrasah (Aliyah dan Tsanawiyah) di Jakarta Timur dan Jakarta Utara yang dipilih melalui proportionate stratified random sampling, menggunakan kuesioner skala Likert lima tingkat yang telah divalidasi (Cronbach's alpha = 0,86). Tahap kualitatif berupa wawancara mendalam terhadap dua belas siswa dan tiga guru Pendidikan Agama Islam, dianalisis secara tematik dan diintegrasikan dengan hasil survei melalui joint display. Regresi linier sederhana menunjukkan pengaruh positif yang signifikan dari paparan algoritma terhadap polarisasi keagamaan (β = 0,559; R² = 0,312; p < 0,001). Siswa dengan paparan tinggi menunjukkan sikap yang lebih eksklusif dan keterbukaan yang lebih rendah, sementara sistem rekomendasi YouTube dan TikTok memperkuat ruang gema dan menggeser otoritas keagamaan dari guru ke figur digital. Penelitian ini mengajukan konsep “keberagamaan algoritmik” untuk menjelaskan orientasi religius yang dibentuk oleh logika seleksi dan amplifikasi pada platform. Karena desain penelitian bersifat korelasional dan paparan diukur melalui laporan diri, temuan ini mengimplikasikan, bukan membuktikan secara langsung, adanya risiko terhadap keterbukaan antaragama; implikasi konkretnya adalah perlunya mengintegrasikan literasi algoritmik dan konten moderasi beragama ke dalam kurikulum madrasah dengan format yang mampu bersaing dengan logika keterlibatan pada platform media sosial.